RESPON VAKSINASI COVID 19 DI SUMATERA BARAT, PERLUKAN TERAPI RASIONAL EMOTIF BEHAVIOUR THERAPHY (REBT) DALAM MELAKUKAN PROMOSI KESEHATAN - Zuwirda; Prima Kurniati Hamzah (Jurnal Endurance, 2023)
The MERS-CoV virus (Corona Virus Covid 19) is a disease found in the lower respiratory tract. The World Health Organization (WHO) in 2019 to 2020 made efforts to prevent transmission by implementing Health protocols, including; washing hands, limiting social movements, wearing masks and vaccinating. In the province of West Sumatra, there are still cities/districts that have not yet reached the national target. 70% Perceptions and desires of the community with health are studied using the Health Belief Model (HBM) theory. The study used a qualitative design with the HBM approach method through interviews and documentation. The research locations are in two regencies: South Solok and Limapuluh Kota. The number of informants there are 6 informants consisting of guardians, people of productive age and people of old age. Based on the results of the study, it is concluded that there is a lack of perception of vulnerability in productive ages because they have a good immune sense; there are hoax news circulating in the community, fear due to Post-Immunization Follow-Up; respondents do not feel the medical benefits of vaccination; poor perception, has an impact on vaccine acceptance that is not optimal. It is necessary to improve communication and more effective health promotion in improving public perception as well as conducting REBT therapy in providing counseling to certain groups in the community so that vaccination targets and objectives are achieved and the creation of heard immunity in the community. Keyword: Response, Vacine, REBT Theraphy.